The Effect Of Nano-Zinc Oxide On Particleboard Decay Resistance - Marzbani, Pouya; Mohammadnia Afrouzi, Younes; Omidvar, Asghar (Maderas. Ciencia y Tecnología, 2015)
The aim of this study was to investigate the decay resistance of particleboards treated with nano-zinc oxide against the white-rot fungus Trametes versicolor and the brown-rot species Coniophora puteana. The nanomaterial was used for manufacturing particleboards at 5, 10 and 15% wt based on the glue dry weight. The soil block decay test was performed according to ASTM D 1413 (2007) using a 12 weeks incubation period. The results showed that all treated boards had good resistance against the decay fungi and the weight loss decreased in the samples with increasing nanomaterial loading. The threshold level of treated boards against fungal decay was obtained about 21% and 17% nano-ZnO against C. puteana and T. versicolor, respectively. Therefore, it had a positive effect on increasing particleboard resistance against the fungi. The maximum decay resistance (or minimum weight loss) occurred in the samples containing 15% zinc oxide nanoparticles.